Heterogeneity of dengue transmission in an endemic area of Colombia. - María Isabel Estupiñán Cárdenas; Víctor Mauricio Herrera; María Consuelo Miranda Montoya; Anyela Lozano Parra; Zuly Milena Zaraza Moncayo; Janeth Patricia Flórez García; Isabel Rodríguez Barraquer; Luis Ángel Villar Centeno (Public Library of Science (PLoS), 2020)
Population based serological surveys are the gold-standard to quantify dengue (DENV) transmission. The purpose of this study was to estimate the age-specific seroprevalence and the force of infection of DENV in an endemic area of Colombia. Between July and October 2014, we conducted a household based cross-sectional survey among 1.037 individuals aged 2 to 40 years living in 40 randomly selected locations in urban Piedecuesta, Santander, Colombia. In addition, we also enrolled 246 indviduals living in rural "veredas". Participants were asked to answer a questionnaire that included demographic, socioeconomic and environmental questions and to provide a 5 ml blood sample. Sera were tested using the IgG indirect ELISA (Panbio) kit to determine past DENV infection. The overall DENV seroprevalence was 70% (95% CI = 67%-71%), but was significantly higher in urban (81%, 95% CI = 78%-83%) as compared to rural (21%, 95% CI = 17%-27%) locations. Age was a major predictor of seropositivity, consistent with endemic circulation of the virus. Using catalytic models we estimated that on average, 12% (95%CI = 11%-13%) of susceptible individuals living in the city are infected by DENV each year. Beyond age, the only predictor of seropositivity in urban locations was prior history of dengue diagnosed by a physician (aPR 1.15, 95% CI = 0.98-1.35). Among participants living in rural settings, those that reported traveling outside of their vereda were more likely to be seropositive (aPR 3.60, 95%CI = 1.54-8.42) as well as those who were born outside of Santander department (aPR = 2.77, 95%CI = 1.20-6.37). These results are consistent with long term endemic circulation of DENV in Piedecuesta, with large heterogeneities between urban and rural areas located just a few kilometers apart. Design of DENV control interventions, including vaccination, will need to consider this fine scale spatial heterogeneity.